Prebiotic- and Panthenol-Containing Multipurpose Healing Dermocosmetics Post-Cryotherapy for Actinic Keratoses: Results of a Randomized Controlled Trial - Cesare Ariasi; Carola Romanò; Cesare Tomasi; Simone Soglia; Gaetano Licata; Luca Rubelli; Piergiacomo Calzavara Pinton; Marina Venturini; Mariachiara Arisi (Dermatology Practical & Conceptual)
Introduction: Actinic keratosis (AK) is a precancerous skin lesion that can progress to keratinocyte carcinoma.